Cholecystoduodenal fistula accompanied by bleeding from the upper gastrointestinal tract (clinical case) - V. M. Manuylov; A. N. Shcherbyuk; D. A. Tsarev; Yu. I. Zakharov; Ya. E. Nemstsveridze; A. V. Mokhov; D. A. Mokhov; E. Yu. Nabieva; S. S. Karpina; U. O. Gafarov; A. V. Peretechikov; A. P. Yunkin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Introduction. Cholecystoduodenal fistula is a rare complication of cholelithiasis and extremely rarely manifests as massive bleeding from the upper gastrointestinal tract. Only 15 similar clinical cases have been described in the world literature. Objective: To present a clinical case of a biliodigestive fistula complicated by upper gastrointestinal bleeding, and to analyze the features of diagnosis and treatment of this pathology. Materials and methods. A clinical case of a 62-year-old patient with cholelithiasis complicated by cholecystoduodenal fistula and massive gastrointestinal bleeding is described. An analysis of literature data with systematization of 15 similar cases was conducted. Results. A patient with a known history of cholelithiasis and biliodigestive fistula developed massive bleeding from the upper gastrointestinal tract with hemorrhagic shock. Endoscopic examinations revealed a fixed hemorrhagic clot and a duodenal bulb ulcer. Despite conservative therapy and endoscopic hemostasis, on the 8th day, rebleeding occurred requiring emergency surgical intervention. Intraoperatively, cholecystoduodenal and cholecystotransverse fistulas with ongoing bleeding were identified. A 2/3 gastric resection with Roux-en-Y reconstruction, cholecystectomy, and right hemicolectomy were performed. Conclusion. Cholecystoduodenal fistula complicated by bleeding requires surgical treatment, as significant bleeding from large arteries is rarely eliminated by conservative treatment or endoscopic hemostasis. The presented case is the 16th in world surgical practice, which emphasizes the need for further study of this pathology and the development of effective treatment methods.